2015
DOI: 10.1002/mdc3.12133
|View full text |Cite
|
Sign up to set email alerts
|

Survey of Health Care Workers Suggests Unmet Palliative Care Needs in Parkinson's Disease

Abstract: The aim of this study was to investigate the knowledge, attitudes, and previous training of Irish health care workers (HCWs) in palliative care in end-stage Parkinson's disease (PD). A survey was distributed to HCWs, including neurologists, geriatricians, general practitioners, nurses, and allied health professionals, in acute and community settings in the Republic of Ireland. Three-hundred and six surveys were returned (32% average response rate). Most HCWs (90%) believed that people with PD have palliative c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
1
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 15 publications
0
23
1
2
Order By: Relevance
“…In this study, many healthcare professionals report different views on palliative care and often equated palliative care with terminal care. Results from the individual and focus group interviews shows that professionals working in PD were not familiar with the WHO definition and more recent insights on palliative care, which was also found in earlier qualitative studies [16][17][18]51]. Discussions about what essential elements are in palliative care for people with PD resulted in several specifications, such as 'discussions about future care' and 'care goals focusing on comfort'.…”
Section: Discussionmentioning
confidence: 79%
“…In this study, many healthcare professionals report different views on palliative care and often equated palliative care with terminal care. Results from the individual and focus group interviews shows that professionals working in PD were not familiar with the WHO definition and more recent insights on palliative care, which was also found in earlier qualitative studies [16][17][18]51]. Discussions about what essential elements are in palliative care for people with PD resulted in several specifications, such as 'discussions about future care' and 'care goals focusing on comfort'.…”
Section: Discussionmentioning
confidence: 79%
“…To develop the interview guide, we first conducted a literature review in PubMed in 2016 using search terms like ‘palliative care’, ‘Parkinson’s disease’ and ‘end of life care’. Our aim was to find relevant studies on persons with PD and (defining) palliative care including expert opinions, case studies and empirical studies [9, 12, 1518, 26–37]. Furthermore, as indicated earlier, we sent out a questionnaire to gain more information on professionals’ knowledge and competence in palliative care.…”
Section: Methodsmentioning
confidence: 99%
“…Health care professionals’ experiences with and perceptions of palliative care in PD are known from a few studies [1518]. It appears that many professionals lack the necessary competences for palliative care, feel inexperienced and want more education in this field [1517].…”
Section: Introductionmentioning
confidence: 99%
“…Four studies reported professionals’ experiences with (the concept of) palliative care and PD [ 25 – 28 ]. Waldron et al showed that professionals often misconceive the putative value of rehabilitation in the palliative care phase.…”
Section: Introductionmentioning
confidence: 99%